A Smart Energy Management System Design for Residential Power Plants - Bayrak, Zehra Ural; Bayrak, Golikay (Gazi Univ, 2017)
In this study, a solar-hydrogen hybrid power generation system is modeled by developing a smart energy management system (EMS) to sustain a continuous power flow for a local load in a constituted residential hybrid power plant. The developed EMS checks the total energy demand of the hybrid power plant and operates the solar power plant or the hydrogen energy based power plant to provide a sustainable power for the local load. A new control card is developed and a real-time EMS is performed in Labview for controlling and monitoring the hybrid system. The implemented electronic control card manages the active power flow of the hybrid system to provide a sustainable power demand of the local load. The current energy demand of the residential power plants can be viable in the lack of the sun or hydrogen, thanks to the developed EMS. The proposed EMS is modeled in Matlab/Simulink, and verified by the experimental study. The experimental results show that the proposed EMS provides a sustainable energy infrastructure for the residential hybrid power plants, and it is also easy implemented and suitable for residential real system applications.
Keywords: Energy management; residential power plants; hydrogen energy; solar energy